A randomized study of sodium hypochlorite versus formocresol pulpotomy in primary molar teeth - John D. Ruby (2018)
Background. Alternatives to vital pulpotomy treatment in primary teeth are being sought because of the high formaldehyde content of traditional formocresol (FC) pulpotomy medicaments. Aim. The aim was to compare the clinical and radiographic success of vital pulpotomy treatment in primary molars using 3% sodium hypochlorite (NaOCl) versus a 1:5 dilution of Buckley's FC. Design. Pulpotomies were performed in primary molars of healthy children between 3 and 10years old. Sixty-five primary teeth were randomized into two groups that were evaluated for treatment outcomes. Following treatment, the pulp chamber was filled with zinc oxide eugenol (ZnOE) and restored with a stainless steel crown cemented with glass ionomer cement. Clinical and radiographic outcomes were recorded at 6 and 12months. Results. The control (FC) and experimental (NaOCl) groups demonstrated 100% clinical success at 6 and 12months. The NaOCl group had 86% (19/22) radiographic success at 6months and 80% (12/15) at 12months. The FC group had 84% (21/25) radiographic success at 6months and 90% (9/10) at 12months. No significant differences were found in the radiographic outcomes between the two groups at 6 and 12months (Fisher's exact test; P=0.574 and P=0.468, respectively). Conclusion. NaOCl demonstrated clinical and radiographic success comparable to FC. © 2012 The Authors. International Journal of Paediatric Dentistry. © 2012 BSPD, IAPD and Blackwell Publishing Ltd.